Few-Layered Boronic Ester Based Covalent Organic Frameworks/Carbon Nanotube Composites for High-Performance K‑Organic Batteries - Chen, Xiudong; Zhang, Hang; Ci, Chenggang; Sun, Weiwei; Wang, Yong (ACS nano, 2019)
Organic electrodes for low-cost potassium ion batteries (PIBs) are attracting more interest by virtue of their molecular diversity, environmental friendliness, and operation safety. But the sluggish potassium diffusion kinetics, dissolution in organic electrolyte, poor electronic conductivity, and low reversible capacities are several drawbacks compared with inorganic counterparts. Herein, the boronic ester based covalent organic framework (COF) material is successfully prepared on the exterior surface of carbon nanotubes (CNTs) via rational design of the organic condensation reaction and used as an anode material for PIBs. The few-layered structure of COF-10@CNT can provide more exposed active sites and fast K+ kinetics. It exhibits ultrahigh potassium storage performances (large reversible capacities of 288 mAh g–1 after 500 cycles at 0.1 A g–1 and 161 mAh g–1 after 4000 cycles at 1 A g–1), which is superior to previous organic electrodes and most inorganic electrodes. Moreover, the K-storage mechanism is proposed to be π-cation interaction between K+ and conjugated π-electrons of benzene rings.